Intensitas Komunikasi dan Mood Pasca Makan terhadap Perilaku Konsumsi Junk Food pada Komunitas Kuliner di Twitter - Putri, Qonita Aristawidya; Syahreni, Nabila Dwi; Erdhika, Kanayla Raffa; Yanti, Avrilia Dewi; Lusiana, Nova (Jurnal Psikologi Integratif, 2025)
The consumption of junk food has been increasing among adolescents and young adults, along with the growth of food-related communities on social media that shape consumption norms and individuals’ emotional experiences after eating. Intense social interactions within online communities and post-meal affective states are assumed to play an important role in reinforcing junk food consumption as part of a lifestyle. This study examined the effects of communication intensity in a Twitter-based food community and post-meal mood on junk food consumption behavior. A quantitative survey method was applied to 103 community members selected through purposive sampling, using the Dutch Eating Behavior Questionnaire (DEBQ), the Food-Related Mood Scale (FDMS), and a researcher-modified communication intensity scale. Multiple linear regression analysis revealed that communication intensity (β=0.443; p<0.05) and post-meal mood (β=0,289; p<0,05) had significant positive effects and jointly explained 38.2% of the variance in junk food consumption behavior. These findings highlight the role of digital communities in shaping consumption norms and emphasize the importance of mood as a trigger in the emotional cycle of eating behavior. Food-related online communities have the potential to be optimized as collaborative nutrition education platforms to promote healthier eating patterns and enhance psychological awareness after consumption.   Perilaku konsumsi junk food semakin meningkat di kalangan remaja dan dewasa muda, seiring dengan berkembangnya komunitas kuliner di media sosial yang turut membentuk norma konsumsi serta pengalaman emosional individu setelah makan. Interaksi sosial yang intens dalam komunitas daring dan kondisi afektif pasca mengonsumsi makanan diduga berperan penting dalam memperkuat kecenderungan konsumsi junk food sebagai bagian dari gaya hidup. Penelitian ini menganalisis pengaruh intensitas komunikasi pada komunitas kuliner di Twitter dan mood pasca makan terhadap perilaku konsumsi junk food. Metode kuantitatif survei diterapkan pada 103 anggota komunitas (purposive sampling) menggunakan instrumen DEBQ (perilaku makan), FDMS (mood pasca makan), dan skala intensitas komunikasi yang telah dimodifikasi oleh peneliti. Analisis regresi linier berganda mengungkapkan bahwa intensitas komunikasi (β=0,443; p<0,05) dan mood pasca makan (β=0,289; p<0,05) berpengaruh positif signifikan, serta secara bersama-sama menjelaskan 38,2% variasi perilaku konsumsi junk food. Temuan menegaskan peran komunitas digital dalam membentuk norma konsumsi serta pentingnya mood sebagai pemicu siklus emosional dalam perilaku makan. Komunitas pecinta kuliner berpotensi dioptimalkan sebagai sarana edukasi gizi kolaboratif untuk mendorong pola makan yang lebih sehat dan meningkatkan kesadaran psikologis pasca konsumsi.